Penganiyaan Terhadap Anak Pasca Sekolah Offline Pada Masa Pandemi Covid 19 - Soehadi, Virley Kezia; Sopacua, Margie Gladies; Latumaerissa, Denny (Faculty of Law, Universitas Pattimura, 2023)
Introduction: The Indonesian government has issued a number of policies to support criminal law enforcement during the Covid-19 pandemic. Children are entrusted by God Almighty who must be guarded and protected as the next generation of the nation and State. Children's rights must also be fulfilled and protected from violence and all forms of discrimination and treatment that are contrary to the general principles of child protection. As for the events that occurred after the Covid 19 pandemic, namely children committing violence against fellow students where the chronology of events was on Monday, October 10, 2022 at around 15.00 WIT, located in front of the Ambon Muhamadiah school in Talake, where the perpetrator FF stopped the victim when he returned home from school and beat the victim using his right and left hands repeatedly on the victim's face and kicked the victim from behind hitting the victim's spine. RS saw the beating and immediately ran towards the victim and also beat the victim using his right fist and left fist towards the back of the victim's head.Purposes of the Research: This study uses normative legal research methods. Peter Mahmud Marzuki, argues that normative legal research which is another name for doctrinal legal research is also known as library research or document study because this research is carried out or shown only on written regulations or other legal materialsResults of the Research: The reasons why children commit violence in the form of maltreatment during the post-pandemic covid 19 online school include; 1) Internal Factors which are divided into; a) the child's own factors where the child has a bad character; b) parental or family factors where the child grows and develops with violence from both parents; c) poverty factors where a person is unable to meet his own needs according to the standard of living; and d) the presence of unwanted children, namely parents who do not anticipate pregnancy so they will do everything in their power to get rid of the child, then 2) External factors consisting of; a) outer circle factors where this factor talks about a bad environment that causes children to commit violence against other children in the form of maltreatment; b) social media where users can easily participate, communicate, share, and create different content without space and time restrictions; and c) cultural factors where they still think that the status of children is underestimated and must be punished if they do not conform to parental expectations.